The effects of literacy on health in Gypsies, Roma and Travellers (GRT): a systematic review and narrative synthesis - Kathryn Charlotte Dixon; Ewen Speed; Montgomery Dunn; Eleanor J C Turner-Moss; Beverley Carpenter; Tanya Blumenfeld (BMJ Global Health)
Introduction Gypsies, Roma and Travellers (GRT) frequently experience poorer health outcomes than the general population and represent the most socially and economically disadvantaged individuals in many countries. In general, GRT in OECD (Organisation for Economic Co-operation and Development) countries have lower rates of literacy than the general population. Although ‘health literacy’ has been examined before, the link between low functional literacy and its effects on health has not yet been explored.Methods Searches were conducted on five large English-language databases for research papers since 2008. Grey literature was included as the number of eligible papers was small. This was complimented by citation ‘chaining’. Study findings of qualitative papers were extracted, codes were devised and then analysed thematically. A narrative synthesis was reported, supplemented by the quantitative findings.Results 15 studies (and two substudies) were analysed. Four strongly overlapping themes were developed: (1) The context of culturally inadequate healthcare systems, (2) psychological impact and disempowerment, (3) intersectional, contextual factors and the unique needs of GRT and (4) considerations for health information resources for GRT patients with low literacy.Conclusion Although low literacy in GRT groups is a well-recognised issue, this is the first systematic review to analyse the link between low literacy and its effects on health outcomes for GRT. The wide range of socioeconomic and cultural factors present in GRT communities, combined with low literacy, act synergistically to worsen the physical and mental health of GRT groups in different ways than that seen in members of the general population with similar low literacy levels. National intervention is required to improve the literacy of GRT children and adults. There is a clear need to develop policies and processes that facilitate a better understanding of literacy levels and how they interact with other social determinants of GRT health among healthcare professionals.Registration number CRD42023468449.